The existent relation between development and entrepreneurial strategies – a preliminary analysis - Nelson Duarte (European Regional Science Association (ERSA), 2003)
Economic growth and development: very popular words nowadays. Why? A large numbers of reasons could be presented to justify this statement, but is enough to say that the world's economy is not living its springtime, since a recession period has started all over the world. Furthermore European Union members have an additional concern: the Union enlargement, and the increase of competitiveness that eastern countries will bring to the market. To increase productivity and competitiveness, the firms as “development agents” play a very important role. However, sometimes these firms are seen as a black box, regarding to the contribution given to development. But is it not important to know weather a firm is following a competitive or cooperative strategy and weather the implications of this strategy affects the development? Usually, when development is the subject in discussion it is very easy to get information about the macro-economic context, the market, competition that firms must face, the entrepreneurial environment (industrial district, clusters, etc.) The main question here is: should not the strategies followed by the firms be considered something extremely important, not only in productivity terms, but also on its contribution to the development (economic, social, or any other)? Would not be important to know and to analyse the choices firms are taking in this competitive environment? Moreover, taking into consideration regional development, and the role that micro firms play on this field, what can one say about the chosen strategies by the entrepreneurs' The objective of this work is to present an analysis of existent to the studies on economic development and, at the same time, to study the references that are presented regarding to the entrepreneurial strategies. The final purpose of this preliminary analysis is to obtain solid information about the state-of-art of both fields, in order to guide a more complete research on the field of development and entrepreneurial strategies.
Keywords: 330